A possibilidade do Recurso de Revista com fundamento em princípios constitucionais de direitos fundamentais e a inadequação da exigência de violação literal ao texto constitucional, contida na alínea c e no parágrafo segundo do artigo 896 da CLT, como requisito à sua admissão - Bicalho, Romeu Gonçalves (2016)
Traditionally, the Law can be seen as a group of norms of conduct created by the infraconstitutional legislature which contain, in their text, in a reasonably clear manner, the identifying elements of the conditions in which they should apply. However, in the past few years, a new form of Law has arisen in Brazil. Contrary to traditional Law, this Law comes straight from the Federal Constitution. The fundamental rights established in the Federal Constitution became a direct source of subjective rights. The currently prevailing thesis states that they should apply directly not only in matters involving the public administration, but also in private relations. The idea of programmatic constitutional norms has lost considerable force. A new constitutional hermeneutic has formed around the interpretation of the fundamental rights. However, the labor law appellate procedure, specifically the Appeal for Review, is not well suited to this new type of right, one that demands a new kind of interpretation. Our proposal seeks to give the art. 896 of the CLT an interpretation in accordance with the Constitution, to achieve greater coherence with this new form of Law and a jurisdiction that promotes the optimization of fundamental rights